Development and External Validation of a Model Predicting Death After Surgery in Patients With a Ruptured Abdominal Aortic Aneurysm: The Dutch Aneurysm Score. (February 2017) - von Meijenfeldt, G.C.I.; van Beek, S.C.; Bastos Gonçalves, F.; Verhagen, H.J.M.; Zeebregts, C.J.; Vahl, A.C.; Wisselink, W.; van der Laan, M.J.; Balm, R.
Abstract : Objective: The decision whether or not to proceed with surgical intervention of a patient with a ruptured abdominal aortic aneurysm (rAAA) is very difficult in daily practice. The primary objective of the present study was to develop and to externally validate a new prediction model: the Dutch Aneurysm Score (DAS). Methods: With a prospective cohort of 10 hospitals ( n = 508) the DAS was developed using a multivariate logistic regression model. Two retrospective cohorts with rAAA patients from two hospitals ( n = 373) were used for external validation. The primary outcome was the combined 30 day and in-hospital death rate. Discrimination (AUC), calibration plots, and the ability to identify high risk patients were compared with the more commonly used Glasgow Aneurysm Score (GAS). Results: After multivariate logistic regression, four pre-operative variables were identified: age, lowest in hospital systolic blood pressure, cardiopulmonary resuscitation, and haemoglobin level. The area under the receiver operating curve (AUC) for the DAS was 0.77 (95% CI 0.72–0.82) compared with the GAS with an AUC of 0.72 (95% CI 0.67–0.77). The DAS showed a death rate in patients with a predicted death rate ≥80% of 83%. Conclusions: The present study shows that the DAS has a higher discriminative performance (AUC) compared with the GAS. All clinical variables used for the DAS are easy to obtain. Identification of low risk patients with the DAS can potentially reduce turndown rates. The DAS can reliably be used by clinicians to make a more informed decision in dialogue with the patient and their family whether or not to proceed with surgical intervention.